Comparative Evaluation of Effect of Auxillary Grooves on Retention of Complete Cast Crowns in Molar Teeth – An In-Vitro Study - Thilak Shetty1, C T Anand2, Sharon Saldanha3, Shobha J Rodrigues4, Umesh Pai3, Mahesh M3, Puneeth He (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim:The aim of this study is to compare and evaluate the effects of auxillary grooves on retention of complete cast crown on molars. Method: Thirty mounted teeth were divided randomly into three groups of 10 each and grooves are placed using NOF104R diamond point. In group A , no groove is placed – control, group B, one groove is placed proximally in the centre of mesial surface – Test group. In group C, two groove is placed proximally , each in centre of mesial surface and distal surface - Test group. Castings were prepared luted and retention was checked using a Universal Testing machine Results were subjected to one way ANOVA and Student T Test. Results: Auxilary retentive features produces a significant increase in retention of complete cast crowns. Incorporation of two proximal grooves on the mesial and distal side produces the most retention as compared to one groove or conventional tooth preparation Conclusion: Retentive features produces a significant increase in retention of complete cast crowns